Efektifitas Model Pembelajaran Kooperatif Tipe Jigsaw Ditinjau dari Motivasi Belajar Matematika Siswa SMP - Ros Santi Wali; La Eru Ugi; Sardin Sardin (Jurnal Akademik Pendidikan Matematika, 2022)
Problem statement of the research was whether cooperative learning model of Jigsaw type was effective viewed from students’ learning motivation in Math at VII grade of SMP Negeri 5 Batauga. The objective of the research was to know the effectiveness of cooperative learning model of Jigsaw type viewed from students’ learning motivation in Math at VII grade of SMP Negeri 5 Batauga. This research was a quantitative research. The research using quasi experimental design. Population of the research was all students of VII grade of SMP Negeri 5 Batauga in odd semester, academic year 2021/2022. There were two classes with the total number of student was 39 students. Sample of the research was all students, which were class VII A as experimental class which taught using Cooperative Learning model of Jigsaw type, and class B as a control class which taught using reguler learning model. Instrument of the research was a questionnaire. Data analysis techniques in this research used descriptive and inferential analysis. The result of the research showed that based on descriptive analysis, it was found that mean score of students’ motivation from experimental class and control class were 18,85 and 10,74. Based on inferential analysis, it could be seen that data was normal and homogeny. Learning motivation data was tested using independent sample test analysis. The result showed that students learning motivation which taught using cooperative learning model of Jigsaw type was in sig. 0.004˂0.05, it meant that H0 was rejected. From this result, it could be concluded that cooperative learning of Jigsaw type was effective viewed from studens’ learning motivation in Math at VII grade of SMP Negeri 5 Batauga.